TiO2 nanotubes grown on Ti substrates with different microstructure - Sopha, Hanna; Tesař, Karel; Knotek, Petr; Jäger, Aleš; Hromádko, Luděk; Macák, Jan (Elsevier, 2018)
Four Ti substrates with various microstructures were investigated for the anodic growth of TiO2 nanotube layers: nanocrystalline and single-crystalline ingots as well as microcrystalline thick Ti sheets and microcrystalline thin Ti foils. All substrates were anodized in a conventional ethylene glycol based electrolyte under identical conditions. The resulting TiO2 nanotube layers were compared in dimensions and the consumption of Ti required for their growth. Unexpectedly, the results showed that on all substrates nanotube layers with a similar thickness and nanotube diameter, as well as a similar degree of ordering and after annealing the same crystallographic orientation of anatase were received, regardless the microstructures. However, the nanotube layers grown on a Ti sheet revealed a slightly higher thickness compared to the other substrates which were assigned to slower field-assisted dissolution rates due to different impurities found in this substrate compared to other ones.
Keywords: titanium; titanium dioxide; nanotubes; anodic oxidation; microstructure